Real estate market analysis : - Brett, Deborah L. (Urban Land Institute, 2009)
Offering the tools needed to evaluate trends and understand key factors affecting the real estate market, this book explains how to get started, where to get information, and how to apply the basic techniques to a variety of development types. This practical primer offers a step-by-step approach to developing property—whether public or private sector—and shows how market-analysis methods have been employed in real projects. The 13 case studies written by top market analysts provide models that can be applied to multifamily, hotel, office, industrial, entertainment, mixed-use, and/or master-planned communities. This is an excellent reference for real estate students and professionals to maximize potential in a troubled market.